ANALISIS KEMAMPUAN BERPIKIR KRITIS DALAM MENYELESAIKAN MASALAH MATEMATIKA SISWA KELAS VIIIC SMP NEGERI 1 KALIBAWANG - Andi Novantoro (Universitas Pekalongan, 2018)
This study aims to determine the level of critical thinking skills in solving mathematics problems students grade VIIIC SMP Negeri 1 Kalibawang Academic Year 2017/2018. Critical thinking was high level thinking, which tag by analyze and need additional explanation. Aspects of critical thinking were basic support, strategy, elementary clarification, advances clarification and make inference. This type of research is qualitative research. Subjects in this study are students of class VIIIC SMP Negeri 1 Kalibawang, consist of 26 students. Technique of collecting data are done by test and interview test. Taking data using the instrument in the form of a description test that have 4 items. Results of student work are examined and grouped into 3 groups, which are high, middle and low groups. Furthermore, interviews are conducted on 6 students purposively, consisting of 2 students per group. Each subject is interviewed based on the student's work, then the interview data is transcript and triangulation is done to test the validity of the data. The result of the research indicates that the result of the analysis of the critical thinking ability in solving the problem of the material description and the volume of building the flat side space of beams and cubes are as follows: (1) building basic skills included in the high category with the percentage of 75,96 %, (2) determining strategy and tactics to solve problems including in medium category with percentage equal to 68,03%, (3) giving elementary clarification including in high category with percentage equal to 75,48% , (4) make advances clarification included in medium category with percentage equal to 68,75%, (5) make inference included in high category with percentage equal to 71,39%.